Fructose-bisphosphate aldolase a is a potential metastasis-associated marker of lung squamous cell carcinoma and promotes lung cell tumorigenesis and migration. - Sha Du (Public Library of Science (PLoS), 2014)
Fructose-bisphosphate aldolase A (ALDOA) is a key enzyme in glycolysis and is responsible for catalyzing the reversible conversion of fructose-1,6-bisphosphate to glyceraldehydes-3-phosphate and dihydroxyacetone phosphate. ALDOA contributes to various cellular functions such as muscle maintenance, regulation of cell shape and mobility, striated muscle contraction, actin filament organization and ATP biosynthetic process. Here, we reported that ALDOA is a highly expressed in lung squamous cell carcinoma (LSCC) and its expression level is correlated with LSCC metastasis, grades, differentiation status and poor prognosis. Depletion of ALDOA expression in the lung squamous carcinoma NCI-H520 cells reduces the capabilities of cell motility and tumorigenesis. These data suggest that ALDOA could be a potential marker for LSCC metastasis and a therapeutic target for drug development.